Contestation of Interests in Nickel Downstreaming Policy In Indonesia: an Analysis of the Advocacy Coalition Framework - Lorenza, Leuryan Cherry; Dewi, Dian Suluh Kusuma; Juwitaningsih, Ekapti Wahjuni D (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research analyzes the contestation of interests in Indonesia's nickel downstreaming policy using the Advocacy Coalition Framework (ACF). Utilizing a qualitative case study method, the study identifies a competition between two primary coalitions: the